2012
DOI: 10.1111/j.1600-0560.2012.01940.x
|View full text |Cite
|
Sign up to set email alerts
|

Sclerotic fibroma (storiform collagenoma)‐like stroma in a fibroadenoma of axillary accessory breast tissue

Abstract: Accessory breast tissue is a subcutaneous remnant persisting after normal embryological development of the breast. It occurs most frequently in the axilla. Fibroadenomas in axillary breast tissue are rare. We report the case of a 29-year-old female patient who presented a fibroadenoma arising in the accessory breast tissue of the right axillary fossa. The neoplasm showed foci of sclerotic fibroma-like stroma. The patient had no signs of Cowden's syndrome. To the best of our knowledge, a lesion of this kind has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…72 Approximately 30 cases of axillary fibroadenoma have been reported in the English-language literature. 5,8,19,[64][65][66][73][74][75][76][77][78][79][80][81] Other lesions occurring in ectopic breast include fibrocystic disease, phyllodes tumor, intraductal papillomas, nipple adenoma, breast hamartoma, and mammary carcinoma. 5,71,76,77,82 The combination of gigantomastia in pregnancy with axillary breast tissue and tumors originating from AGMLG occurs very rarely and can be confused clinically with inflammatory breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…72 Approximately 30 cases of axillary fibroadenoma have been reported in the English-language literature. 5,8,19,[64][65][66][73][74][75][76][77][78][79][80][81] Other lesions occurring in ectopic breast include fibrocystic disease, phyllodes tumor, intraductal papillomas, nipple adenoma, breast hamartoma, and mammary carcinoma. 5,71,76,77,82 The combination of gigantomastia in pregnancy with axillary breast tissue and tumors originating from AGMLG occurs very rarely and can be confused clinically with inflammatory breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Val-Bernal et al ( 9 ) reported a case of a fibroadenoma in axilla with of SF-like stroma and that was located within accessory breast tissue. In our case, however, there was no evidence of accessory breast tissue or the tumor was not changed from fibroadenoma.…”
Section: Discussionmentioning
confidence: 99%
“…Other possible differential diagnosis includes dermatofibroma, in which changes similar to SF have been described, but with CD34 negativity . Lesions histologically resembling SF have also been described in a fibroadenoma of axillary accessory breast tissue, in sclerotic lipomas, and in certain inflammatory conditions, such as chronic folliculitis, but none of these lesions contained concentric lamellar structures.…”
Section: Discussionmentioning
confidence: 99%